IDENTIFIKASI SOCIAL CAPITAL DALAM UPAYA OPTIMALISASI PENDAPATAN ZAKAT - Monika Guswila Sari; Warsito Kawedar (Diponegoro Journal of Accounting, 2023)
This study focused on the social capital of the National Amil Zakat Agency in an effort to optimize zakat income and find out how the environmental, social and organizational governance are. This research is expected to provide useful information for the community and for the National Amil Zakat Agency (BAZNAS) Semarang City. The research method used in this study is a qualitative approach. The data used are primary data obtained directly from the results of in depth semi-structured interviews with informants who are representatives of each element of the Semarang City BAZNAS functionaries, donors (muzaki) and beneficiaries (mustahik). The results showed that BAZNAS Semarang City has a solid social capital, judging from the three dimensions that build it, namely the cognitive dimension, the relational dimension, and the structural dimension. BAZNAS Semarang City has built trust, cooperation, norms, values and a positive attitude. Able to utilize good communication and information with external and internal parties. Have a well-managed separation of functions, and operational activities that are in accordance with regulated regulations. The social capital built by BAZNAS Semarang City is effective in optimizing zakat fund income as seen from the growth every year. The suggestion of this research is the need for support from the Semarang City government by providing clearer and binding rules regarding the uniformity of zakat payments from government employees to the Semarang City BAZNAS so that the zakat funds collected can be more optimal.